Efektivitas Media Papan Pintar Terhadap Pemahaman Konsep Materi Satuan Waktu di SD - Fitri Indriyanti Indriyanti (Jurnal THEOREMS (The Original Research of Mathematics), 2023)
This research is motivated by a problem of the low math skills of students in elementary schools. The purpose of this research is to find out how far the effectiveness of the smartboard media is in understanding the concept of the unit time material for students in elementary schools. The research method experimental which a quasi-experimental design (Quasy-experiment). The population of this study was an elementary school located in Tasikmalaya City, using a purposive sampling technique. The data collection technique used is in the form of a test given through the pre-test and post-test. Based on the results of the descriptive statistical analysis and the results of the inferential statistical analysis it was proven that the understanding of the experimental class that was given treatment was better than the control class. This is evidenced by the acquisition of an average value of Sig.(2-tailed) of 0.004, where 0.004 <0.05. This means that Ha is accepted and Ho is rejected, which means that the average post-test final score for the experimental class using smart board media is different from the average post-test final score for the control class without using smart board media. Based on the quality of understanding improvement in the experimental class is in the medium category, while the quality of understanding improvement in the control class is in the low category. So it was concluded that the smart board media effectively influenced the understanding of the concept of time unit material for third grade elementary school students.